2020
DOI: 10.3390/microorganisms8071012
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Ultrastructural Signatures of K+-Induced Aggregation in Phytophthora parasitica Zoospores

Abstract: Most pathogenic oomycetes of the genus Phytophthora spread in water films as flagellated zoospores. Zoospores perceive and produce signals attracting other zoospores, resulting in autoaggregation in vitro or biofilm formation on plant surface. The mechanisms underlying intercellular communication and consequent attraction, adhesion and aggregation are largely unknown. In Phytophthora parasitica, the perception of a K+ gradient induces coordinated motion and aggregation. To define cellular and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 82 publications
(117 reference statements)
0
19
0
Order By: Relevance
“…The availability of gene sequences and mRNA-level quantification data generated by the different Phytophthora genome projects has had a massive impact on the definition and the classification of the molecular repertoire at different stages of the Phytophthora life cycle, including zoospores [2] . Several studies have indicated the occurrence and the importance of putative pumps, ligand-gated channels, tyrosine kinase-like and G-protein signaling [32] , [66] , [67] in Phytophthora . Nevertheless, to date, very little is known about the major classes of receptor and signaling pathways involved in environment perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of gene sequences and mRNA-level quantification data generated by the different Phytophthora genome projects has had a massive impact on the definition and the classification of the molecular repertoire at different stages of the Phytophthora life cycle, including zoospores [2] . Several studies have indicated the occurrence and the importance of putative pumps, ligand-gated channels, tyrosine kinase-like and G-protein signaling [32] , [66] , [67] in Phytophthora . Nevertheless, to date, very little is known about the major classes of receptor and signaling pathways involved in environment perception.…”
Section: Discussionmentioning
confidence: 99%
“…However, the capacity of Phytophthora species to release 10 5 -10 6 zoospores per infected plant in controlled conditions [16] , [31] is indicative of their ability to induce radical change in the explored soil environment. For example, the 30-fold upregulation of a gene encoding a secreted alpha carbonic anhydrase (α-CA), observed in P. parasitica zoospores upon aggregation establishment [32] , together with the oomycete’s ability to produce a high-density inoculum in proximity of the target [16] , suggests a potential and transitory role of this zoospore enzyme in non-photosynthetic CO 2 fixation. A recent study showed that soil CA activity varied with the diversity of microbial communities and CA gene expression patterns [33] .…”
Section: The Soil Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, potassium, which is uptaken by roots in the soil, reduces zoospore swimming speed, causes immediate directional changes and also results in perpetual circle trajectories [17, 18]. Bassani et al provide transcriptomic studies showing that potassium induces zoospore aggregation, which facilitates the advantages for zoospores to attack the host-root [19]. Experimental evidence has demonstrated that zoospore-zoospore interaction can lead to “pattern swimming”, a microbial bioconvection happened without the appearance of chemical or electrical signals [20, 21].…”
Section: Figmentioning
confidence: 99%
“…Bassani et al . provide transcriptomic studies showing that potassium induces zoospore aggregation, which facilitates the advantages for zoospores to attack the host-root [19].…”
mentioning
confidence: 99%